The group size and density of long-tailed macaque (Macaca fascicularis) (primates: cercopithecidae) in oil palm production landscapes - Tee, Sze Ling (2016)
Expansion of oil palm (Elaeis guineensis) industry in Malaysia is one of the major threats that has caused biodiversity loss and fragmentation of forest areas. Macaca fascicularis is an example of primate species that being negatively affected by oil palm agriculture but not much attention is being paid to this common species. The effects brought by oil palm monocultural plantations can be explained through understanding the population size of long-tailed macaque in large-scale oil palm plantations. The main objective of this study is to determine the effect of oil palm production on the population of M. fascicularis. A census of long-tailed macaque had been conducted between January to February 2016 to determine the mean troop size of macaque in a large-scale oil palm plantation with a total area of 1689.531 hectares. A total number of 13 groups with 98 individuals were recorded. The density of long-tailed macaque within the oil palm plantation area was 5.68 individuals per 100 hectares. One sample t-test, two sample t-test, and two-sample Poisson test were used to analyze the collected data. The mean group size of long-tailed macaque in large-scale oil palm plantation with that in oil palm smallholdings (t = 4.70), primary forest (t = -7.32), and secondary forest (t = -9.22) had a significant difference (p < .001). The comparison between adult abundance and juvenile abundance in large-scale oil palm plantation showed a slightly significant difference (p = .043) with the simple normal approximation of -2.020. The comparison between adult abundance and juvenile abundance in smallholdings was significantly different (p < .001). There was a significant difference (p < .001) in adult abundance between large-scale oil palm plantation and oil palm smallholdings (t = -6.58). However, there was no significant difference (p = .05) in juvenile abundance between large-scale oil palm plantation and oil palm smallholdings (t = 2.13). The negative impacts brought by oil palm production to long-tailed macaque population are more severe in large-scale plantation than in oil palm smallholdings. Large-scale oil palm monocultures should be minimized or limited as it causes adverse impacts on biodiversity including common species such as long-tailed macaque.